Economic Philosophy and Constitution Making in Nigeria (Journal of Management and Social Sciences, 2019)
The analyses of constitutions, except in few instances, tend to be legalistic on the basisof examining the structures, functions and perhaps provisions on fundamental humanrights that are contained in the document. A section by section legalistic interpretationof constitution making in Nigeria has tended to be devoid of the laying bare of thedivergent interests in society in the epoch when the constitution was made and thesubsistence of the dominant economic interests. To analyse constitution making inNigeria this way is faulty. To incorporate an analysis of the dominant interests insociety into constitution making is to understand that constitutions are not reflective ofthe interests of all in society but an instrument to protect property and economic modeof accumulation of the dominant class interests. An analysis of constitution makingunder the military dictatorships in Nigeria, starting with the 1979 through to the 1989and 1999 constitutions support the position that these constitutions were made toprotect property interests and a capitalist mode of economic accumulation.